Unmanned aerial vehicle systems: key management and intrusion response techniques - Reshma C. Sonawane; A. Muthukrishnan (Institute of Advanced Engineering and Science, 2026)
Protecting information is crucial for unmanned aerial vehicle (UAV) network communications, particularly during delicate tasks such as surveillance and reconnaissance. While encryption safeguards data privacy, managing and distributing keys in UAV settings poses significant challenges due to the vehicles' mobility and limited processing power. This research proposes an efficient key management scheme utilizing elliptic curve cryptography (ECC) and bilinear pairings, complemented by a lightweight intrusion detection system (IDS). The method employs behavior-based anomaly detection, using cluster-based watchdogs and trust assessment to identify and isolate harmful nodes. Additionally, applying compression techniques before encryption helps to reduce transmission load. Simulation in NS2 demonstrates performance improvements of 6-10% in throughput, 4-6% in packet delivery ratio (PDR), and a 13-17% reduction in delay compared to elliptic curve cryptography Diffie–Hellman (ECCDH) and pairwise encryption methods.